Modelo de avaliação da maturidade para o banking 4.0: proposta e aplicação em um banco brasileiro - Soares, Séfora Maria Nunes (2023)
Recent technological innovations are changing the way we produce and consume. Relationships with customers are closer as connectivity and access to information have increased the level of demand for personalized products and services. These radical changes permeated all sectors of society and were associated with the German concept of Industry 4.0 (I4.0) linked to a conceptual relationship with the 4th Industrial Revolution. With the banking sector it was no different from the digitalization of service, active offer and consumption profile analysis are examples of practices of the so-called Banking 4.0 (B4.0). In this scenario, this research's main objective is to develop a maturity model for the implementation of Banking 4.0. From a systematic literature review (RSL), 16 technologies were identified, including e-commerce, fintechs and open-banking, for example, and practices that were linked to the use of these technologies and little associated with I4.0. Furthermore, from an RSL, we provide that Maturity Assessment Models (MM) are validated tools in the context of measuring the degree of implementation of I4.0 in the manufacturing sector, and can be adapted to any context. Generally, MMs consist of a sequence of maturity levels that represent a path of evolution, with the objects of analysis being evaluated in several conceptual dimensions according to their application context. Through this RSL, we list the main dimensions and levels found in the literature for manufacturing and which, in an adaptive way, supported the formulation of the MM for B4.0. Thus, after understanding the particularities of B4.0 and the dimensions and levels of an MM, it was possible to prepare an initial proposal for an MM for B4.0, with 5 dimensions, 4 levels and 42 maturity items. This model was evaluated by experts on the subject, resulting in a refinement of the model. With this improved tool, a case study was carried out in a Brazilian Bank in order to validate the proposed model. Respondents were able to assess the degree of importance of maturity items and the Bank's performance, generating data to obtain the Institution's Global Maturity. In the end, it was possible to affirm that the model is suitable for application in Banks as the interviewees positively evaluated the proposal, managing to identify the institution's performance within the maturity items and suggesting improvements to the model. The research contributes to the theory by having a pioneering nature in the formulation of a MM for B4.0, with a model evaluated by experts, as well as contributing to financial institutions in the holistic evaluation of the implementation of B4.0 in favor of better performance of result.